The immune response of Atlantic cod (Gadus morhua L.) - Bergljót Magnadóttir 1943- (2014)
Interest in cod aquaculture has been growing over the last few decades, resulting in varied research on cod aimed at optimising conditions for both growth and survival. Cultural conditions may increase the danger of infections. Disease control by vaccination has proved successful in the farming of several fish species. However, cod do not respond well to vaccination. Recently it was shown that the fish lacks an antigen presenting mechanism (MHC class II molecules) and T helper cells; these are considered critical elements for developing a specific antibody response and, hence, successful vaccines. The immune response of cod to immunisation, infection and other stimuli is reviewed in this paper. Cod has an effective innate immune system and elements of the adaptive system that show unusual diversity and abundance. The defect in the cod's immune system is of great interest in comparative and evolutionary immunology and calls for a new approach to vaccine development and vaccine strategies in cod aquaculture. Vaxandi áhugi hefur verið á þorskeldi á síðustu áratugum sem hefur leitt til margs konar rannsókna á þorski í þeim tilgangi að efla vöxt og heilbrigði í eldi. Þéttleiki fisks í eldi eykur hættu á sýkingum. Bólusetningar hafa gefið góða vörn gegn sjúkdómum í eldi margra fisktegunda. Hins vegar, kom í ljós að þorskurinn svarar ekki vel bólusetningu. Nýlega var sýnt fram á að þorskinn vantaði ákveðnar vefjaflokkasameindir (MHC af flokki II) og T-hjálparfrumur sem eru lykilþættir við myndun mótefna og góðs árangurs bólusetningar. Í þessari yfirlitsgrein er gert grein fyrir ónæmisviðbrögðum þorsks við bólusetningu, sýkingu og öðru ónæmisáreiti. Þorskurinn hefur öflugt meðfætt ónæmiskerfi og þættir í áunna kerfinu sýna óvenju mikla fjölbreytni. Gallinn í ónæmiskerfi þorsk er áhugaverður með tilliti til samanburðar og þróunarsögulegra rannsókna en, ekki síst, kallar á nýja nálgun á þróun bóluefna og aðferða við bólusetningar í þorskeldi.